Comparison of paramedic competencies in the Czech Republic, Poland, Slovakia and Germany - Žďára, Jaroslav; Kusák, Jiří (Vojenské zdravotnické listy, 2025)
The profession of paramedic has become an integral part of the health care delivery system in the Czech Republic. It is a profession belonging to the group of regulated professions, with clearly defined rules for education and practice itself.This study attempted to map how the competences and professional training methods of RNs differ in the Czech Republic, Poland, Germany and Slovakia, which are the closest states to the Czech Republic and also have a similar approach to the pre-hospital care system. There is a real assumption that the principles of training paramedics and their competence will not differ significantly within these EU states. The study was carried out as a research, overview. A content analysis of the current legislation was carried out, regarding the education and work content of paramedics in the environment of the Czech Republic, Germany, Poland and Slovakia.As part of the comparison of these states, it was found that the education and the system of activity of a paramedic differ in details, given by national legislative specifics. Especially in the areas of ZZ competences, it was found that paramedic is the most limited in the conditions of the Czech Republic. However, these limits should not have a major impact on the quality of care provided within the prehospital care, due to the dense network of RZP stations and the low arrival times of crews with doctors.
Keywords: odborná způsobilost; lidé; zdravotničtí záchranáři; Germany; kvalita zdravotní péče; urgentní zdravotnické služby; Slovakia; Emergency Medical Services; Poland; zákonodárství jako téma; Quality of Health Care; Humans; Slovenská republika; vzdělávání odborné; Health Services Accessibility; Česká republika; Professional Competence; Legislation as Topic; Education, Professional; dostupnost zdravotnických služeb; Czech Republic; Polsko; Německo; Paramedics